2011
DOI: 10.1007/s10816-011-9103-6
|View full text |Cite
|
Sign up to set email alerts
|

A Twenty-First Century Archaeology of Stone Artifacts

Abstract: Archaeologists today, as in the past, continue to divide their stone artifact assemblages into categories and to give privilege to certain of these categories over others. Retouched tools and particular core forms, for instance, are thought to contain more information than the unretouched flakes and flake fragments. This reflects the assumption that information to be gained from stone artifacts is present within the artifact itself. This study evaluates a continued interest in the final form of stone artifacts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(49 citation statements)
references
References 64 publications
1
48
0
Order By: Relevance
“…Some rock shelter sites show the reuse of already patinated blanks or the introduction of naturally broken pieces of flint, geofacts picked up en route and used as blanks for tool production. This relaxed attitude toward tool blanks is comparable to what has been documented in the Australian record (85), whereas also earlier phases of the Upper Paleolithic-including the Aurignacian-show strong similarities to Middle Paleolithic raw material strategies, at least in the wellstudied Aquitaine basin in southwestern France (84).…”
Section: Neandertal Ways Of Lifesupporting
confidence: 79%
“…Some rock shelter sites show the reuse of already patinated blanks or the introduction of naturally broken pieces of flint, geofacts picked up en route and used as blanks for tool production. This relaxed attitude toward tool blanks is comparable to what has been documented in the Australian record (85), whereas also earlier phases of the Upper Paleolithic-including the Aurignacian-show strong similarities to Middle Paleolithic raw material strategies, at least in the wellstudied Aquitaine basin in southwestern France (84).…”
Section: Neandertal Ways Of Lifesupporting
confidence: 79%
“…Technological analyses are being combined with interpretive approaches that draw on the fundamental principles of evolutionary ecology to provide insights into the circumstances in which different strategies were employed to acquire raw material, fashion it into tools and to repair or replace those tools (e.g. Clarkson, 2007, Holdaway andDouglass, 2012). The application of these approaches to stone artefacts from Lake Mungo has demonstrated that significant shifts in technological strategies can be represented by quite subtle changes in assemblage characteristics (Tumney, 2011, Stern et al, 2013, Spry, 2014.…”
Section: Discussionmentioning
confidence: 99%
“…We are mindful of the fact that we are dealing with a regional palimpsest with much loss or mixing of material through a time depth of 1 million years or more, and with a record that is generally of low resolution (Rossignol and Wandsnider, 1992;Bailey et al, 1997;Bailey, 2007;Fanning et al, 2009, Holdaway andFanning, 2010;Holdaway and Douglass, 2011). The technological and typological character of the tools themselves may provide chronological clues, but these depend on assumed correlations with stratified and dated material elsewhere, and provide only very broad indications of date.…”
Section: Survey Strategy and Methodsmentioning
confidence: 99%